The time is now: why we must identify and address health disparities in sport and recreation injury - Charlotte Baker; Oziomachukwu Chinaka; Elizabeth C. Stewart (BMC, 2021)
Abstract Background Social and structural determinants of health (SDOH) are the conditions in which individuals are born, live, learn, work, play, worship, and age. These drivers of health are integral in contextualizing the understanding and prevention of sport and recreation injury (SRI), and recognizing their impact is necessary to provide a complete and accurate picture of health and health outcomes related to injury. Main Reducing disparities and achieving equity in sports and recreation is possible in part by improving data collection methodologies and utilization. Often, many SDOH have considerable effect on SRI. Although SRI epidemiology frequently examines differences by sex, there is limited inclusion of factors such as socioeconomic status, housing, gender, and food security, in sport specific data sources or in analysis of sport recreation and injury using other sources (e.g. administrative data). The ongoing dual epidemics in the United States - racism and COVID-19 - have emphasized the importance of having and utilizing SDOH data to reduce the burden of injury and disproportionate effects on our diverse population. Conclusion Moving forward, to address disparities in SRI, SDOH must be included as a part of research priorities, health related goals, and policies. This difference can be made in developing consistency in data collection and utilization. This will provide an accurate picture of the intersections and interdisciplinary changes required to design the best approach to problems to develop solutions. Future data collection and utilization should prioritize SDOH.